695 Photo-otoscopy Audit: A Review of Change in Departmental Practice Due to COVID-19. (12th October 2021) - Chan, K Y; Thornton, H; Gordon, C; Ishii, H; Clark, M
Abstract: Background: Photo-otoscopy is a new service set up during the COVID-19 pandemic, with the view to minimise unnecessary appointments, protect vulnerable patients, and optimise efficiency of ENT-outpatient appointments. The objectives are to assess rate of diagnostic photos and investigate how to improve this service. Method: First cycle was performed between June and July and second cycle between October and December 2020. All patients attending Audiology who had a photo taken were included. Photos were analysed based on a number of variables to identify the proportion of diagnostic and non-diagnostic photos. First cycle highlighted a few changes to practice that were then instigated for second cycle. Results: 324 patients and 232 patients were included in first and second cycle respectively. 17 operators/audiologists were involved. There is slight improvement in percentage of diagnostic photos in second cycle compared to first (30.6% to 31.9% in right ear and 23.5% to 35.8% in left ear). Percentages of non-diagnostic photos with blurriness as sole reason have increased compared to first cycle. Percentages of non-diagnostic photos with all 3 variables present have reduced significantly. Mean percentage of acceptable photos per operator have also improved. 8 out of 10 ENT consultants/registrars found the service useful. Conclusions: Rate of diagnostic photos remained low (<40%) despite implementation of changes to practice from first cycle. 38% of non-diagnostic photos were wax-related. There is significant variation in rate of diagnostic photos due to its operator-dependent nature. Given the expansion of telemedicine, there is definitely scope for future development for photo-otoscopy.